Outcomes in CME/CPD – Special Collection: Effect Size Benchmarking for Internet-based Enduring CME Activities - Olivieri, Jason J (J Eur CME, 2020)
The volume of certified, internet enduring materials produced per year has nearly doubled in the last decade. Meta-analyses indicate that Internet-based education for clinicians is effective; however, the relevance of these studies to the nearly 50,000 such activities certified per year is questionable. Effect size is one metric by which CME providers may assess effectiveness, but caution must be used in comparing effect size data with external benchmarks such as peer-reviewed literature. This report presents a pooled standardised mean difference (Cohen’s d) for 40 accredited, Internet-based enduring materials produced between 2016 and 2018. Data suggests that a Cohen’s d between 0.48 and 0.75 may be a useful benchmark. Benchmarks reported in the literature for this format are notably higher. The limitations of comparison to such benchmarks are considered.